Miniature Diversity in Bumi Gora Dormitory NTB: As a Reflection of Multicultural Dynamics Awareness in West Nusa Tenggara - Baehaki (ASTEEC, 2024)
NTB Dormitory is a residence for students from the NTB province in Yogyakarta, this dormitory contains 41 students who study at several campuses in Yogyakarta. Students of NTB province consist of three different tribes namely Sasak Tribe, Samawa Tribe, and Mbojo Tribe. These three different cultural backgrounds live in harmony in one place, namely the NTB dormitory. This research aims to answer the problem of how the activities of NTB dormitory students and how the daily influence of NTB dormitory on Multicultural attitudes. The method used in this paper is a qualitative method whose data is obtained through observation and interviews. The theory used to approach this case is Berger's social construction theory. Where in Berger's view reality is formed from three dialectics namely internalisation, externalisation, and objectivation. Furthermore, the findings in this paper related to the activities of the NTB dormitory community can be seen from the activities made from the dormitory such as cleaning programmes, weekly meetings, yasinan and other activities that are most dominant are going to lectures, gathering discussions and hanging out. The daily lives of these students form an awareness of unity and a tolerant spirit. Because of the imagi in individuals who think that fellow NTB dormitory communities are people who have the same fate and the same neighbourhood. Even though their backgrounds have not previously known each other.